Role of early surgical intervention in outcome and prognosis of spontaneous cerebellar hemorrhage with intraventricular extension - Maharjan, Jemesh Singh (Eastern Green Neurosurgery, 2021)
Spontaneous cerebellar hematomas represent 5 to 13% of all cases of spontaneous intracranial hemorrhage. The main controversy involves deciding which cases require surgical evacuation of the hematoma versus other options, such as ventricular drainage only or conservative treatment. Furthermore, because the clinical course is variable in some cases, timing of such treatment should be carefully considered. The duration from the onset of hemorrhage also plays an important role in prognosis and recovery of the patient. Both the clinical presentation and subsequent course vary among cases. Unpredictable rapid deterioration in consciousness levels has been recognized. The majority of patients with such decline in consciousness experience the deterioration primarily within 72 hrs after onset⁠. Acute presentation was observed to be correlated with poor outcomes. In our report, the first case presented with sudden onset of headache in the right frontal region of head with vertigo. He came to hospital within 6 hours of onset. However, the second case had an onset of symptoms around 72 hours before the presentation.